D-methionine (D-met) significantly reduces kanamycin-induced ototoxicity in pigmented guinea pigs. (3rd May 2016) - Campbell, Kathleen C. M.; Martin, Seth M.; Meech, Robert P.; Hargrove, Tim L.; Verhulst, Steven J.; Fox, Daniel J.
Abstract: Objective: Test D-methionine (D-met) as an otoprotectant from kanamycin-induced ototoxicity and determine the lowest maximally protective D-met dose. Design: Auditory brainstem responses (ABR) were measured at 4, 8, 14, and 20 kHz at baseline and two, four, and six weeks after kanamycin and D-met administration initiation. ABR threshold shifts assessed auditory function. Following six-week ABR testing, animals were decapitated and cochleae collected for outer hair cell (OHC) quantification. Study sample: Eight groups of 10 male pigmented guinea pigs were administered a subcutaneous kanamycin (250 mg/kg/dose) injection once per day and an intraperitoneal D-met injection (0 (saline), 120, 180, 240, 300, 360, 420, or 480 mg/kg/day) twice per day for 23 days. Results: Significant ABR threshold shift reductions and increased OHC counts (p ≤0.01) were measured at multiple D-met-dosed groups starting at two-week ABR assessments. A 300 mg/kg/day optimal otoprotective D-met dose provided 34–41 dB ABR threshold shift reductions and OHC protection. Lesser, but significant, D-met otoprotection was measured at lower and higher D-met doses. Conclusions: D-met significantly reduced ABR threshold shifts and increased OHC percentages compared to kanamycin-treated controls. Results may be clinically significant particularly for multidrug-resistant tuberculosis patients who frequently suffer from kanamycin-induced hearing loss in developing countries.